Dualband microstrip antenna (2.4GHz & 5.8 GHz) with novel back transmission line feed technique - Md. Fazlul, Hasan (Universiti Malaysia Sarawak, 2019)
Antenna plays a very significant role in wireless communication system. Day by day antenna is developing very fast to be used in various kind of application. Analysis and design of different types of antenna leading crucial parts for wireless applications. Microstrip antenna is a low profile and popular antennas that has been designed and being used in many important areas of the applications. Microstrip antenna is designed by Microstrip technology. It only works with microwave frequency. These are very useful with their relative applications. Feeding technique is very important to design microstrip antenna. From past researchers, they have designed and developed microstrip antenna by using different types of feed technique. Feeding technique is used to create the results of S i, i parameter. Such as, return loss, resonance frequency, radiation pattern. In this project, it has been designed a dual band microstrip antenna at 2.4 GHz and 5.8 GHz with novel back transmission line feed technique. The most interesting and main part of this project is using a new feeding technique to get Si, i parameter result with less harmonics. Harmonics create an effect on the bandwidth because harmonics is not same with the magnitude of resonance frequency. So, this project has found the way to solve the problem by using novel back transmission line feed technique in microstrip antenna and compared between novel back transmission line feed technique with transmission line inset feed technique. The concluding design of dual band antenna is fabricated by using PCB technology.